Kitab Berladang: A Portrait of Hybrid Islam in West Kalimantan - Amin, Faizal (Studia Islamika, 2013)
Kitab Berladang is a manuscript from Putussibau, located in the interior of West Kalimantan. The text describes the ritual practices of the Muslim–Dayak community in rice cultivation activities. The dynamic mixing of elements from traditional culture of the Kapuas Hulu people and the teachings of Islam has resulted in a hybrid form of local Islam. Kitab Berladang, which provides a portrait of the diversity of the Muslim–Dayak community in West Kalimantan, outlines a hybrid character of Islam that can be seen in three domains. Firstly, in how the structure of the ritual of swidden cultivation retains the traditional procedures and also utilizes verses from the Holy Qur’an and Hadith. Secondly, in the incorporation of vocabulary and terminology from the local language with Arabic. Thirdly, in the reinterpretation of the symbols that were originally derived from legends and myths about rice in the community’s system of traditional beliefs, along with Islamic concepts derived from the tradition of theological and mystical thought.DOI: 10.15408/sdi.v20i1.349